perkembangan,peserta didik,afekt TAHAP PERKEMBANGAN AFEKTIF PESERTA DIDIK: TAHAP PERKEMBANGAN AFEKTIF PESERTA DIDIK - Ma'ruf, Abd Rahman K.; Bala , Yurike (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
This article discusses the stages of affective development of students. Affective development is an important part of student development, which influences the way they think, act, and interact with others. This article explains the understanding of student development and the stages of student affective development. This article is presented using a qualitative method which presents a description of qualitative data. The development of affective students is a development related to the emotional and psychological aspects of students. Affective development includes changes in the attitudes, values, beliefs, and emotions of students. The affective aspect also includes students' ability to understand, manage, and express their emotions well, as well as their ability to develop healthy and positive relationships with other people. Affective development can be influenced by a variety of factors, including the social environment, family, and educational experiences. Therefore, educators must pay attention to the affective development of students and provide appropriate support to help them grow and develop emotionally. From the explanation of the stages of affective development in students, it can be concluded that emotion and affective development play an important role in the teaching-learning process and children's academic success. Therefore, teachers and parents need to understand the stages of affective development in children and provide appropriate support to help children develop their affective aspects. But keep in mind that every child has a different pace and pace of development, so a sensitive and responsive approach must be used to help each child individually.